1991
DOI: 10.1111/j.1365-2621.1991.tb05304.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fermentative Bacteria in a Model Low Salt Cucumber Juice Brine

Abstract: Bifdobacterium bifidum, Lactobacillus casei, Lacrobacillus plantarurn, Lactococcus diace@actis, Leuconosroc mesenteroides, Leuconostoc oenos, Pediococcus pentosaceus and a mixed culture of Propionibacterium shermanii and P. pentosaceus were used to ferment a model low salt (2.5% NaCI) cucumber juice brine at 22-26°C for 39 days. Pcrccnt sugar fermented ranged from 16.2 to 87.7. Substrates were citric acid, fructose, glucose and malic acid. Fermentation products quantitated were acetic acid, acetoin, ethanol, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…From the final concentrations of lactic and acetic acids, lactic to acetic ratios of 3.0 and 5.6 were obtained for spontaneous and controlled fermentation, respectively. A high ratio of volatile to nonvolatile acids appears to have a positive effect on flavor, as observed for sauerkraut (Trail et al, 1996), cucumbers (Chavasit et al, 1991), and kimchi (Fleming et al, 1995). However, this has not yet been demonstrated in olives.…”
Section: Microbiological Changes During Fermentationmentioning
confidence: 93%
“…From the final concentrations of lactic and acetic acids, lactic to acetic ratios of 3.0 and 5.6 were obtained for spontaneous and controlled fermentation, respectively. A high ratio of volatile to nonvolatile acids appears to have a positive effect on flavor, as observed for sauerkraut (Trail et al, 1996), cucumbers (Chavasit et al, 1991), and kimchi (Fleming et al, 1995). However, this has not yet been demonstrated in olives.…”
Section: Microbiological Changes During Fermentationmentioning
confidence: 93%
“…Some studies have reported the effects of several chloride salts on microbial growth in cucumber extracts (Naewbanij and others ; Chavasti and others ). Guillou and others () produced good quality pickles when moderate amounts of NaCl (5%) and CaCl 2 (0.2%) were present together with potassium sorbate (0.2%).…”
Section: Reduction Of Salt In Vegetable Productsmentioning
confidence: 99%
“…2009), respectively. Past sensory characterization studies on fermented products like cucumber juice (Chavasit et al . 1991) and bittergourd and fenugreek leaves (Gupta et al .…”
Section: Resultsmentioning
confidence: 99%